Removal of Lead (II) from Aqueous Solution Using Cocopeat: An Investigation on the Isotherm and Kinetic - Abollfazl Shakeri; Nourallah Hazeri,; Jafar Valizadeh; Esmail Hashemi; Ali Reza Motavalizadeh Kakhky (Iranian Journal of Chemistry & Chemical Engineering, 2012)
The aim of the present work was to investigate the ability of Cocopeat to remove of lead (II) from aqueous solutions. The effects of different parameters such as particle size, adsorbent dosage, pH, contact time, agitation speed and concentration on the removal process has been investigated. The maximum removal of lead ion (92.5%) took place in the pH range of 4 contact time in 30 minutes and initial concentration of 30 mg.L-1. Results indicated that the Langmuir model gave a better fit to the experimental data in comparison with the Freundlich equation. The process followed pseudo-second-order kinetics.